Epigenetic regulation of NKG2D ligand and the rise of NK cell-based immunotherapy for cancer treatment - Kumar, Raj; Gupta, Romi (Frontiers in Oncology, 2024)
Epigenetic modifications influence gene expression and effects cancer initiation and progression. Therefore, they serve as diagnostic and prognostic biomarkers and potential therapeutic targets. Natural Killer (NK) cells, integral to the innate immune system, exhibit antitumor effect by recognizing and eliminating cancerous cells through the balance of activating and inhibitory ligands. Understanding the epigenetic regulation of NK cell ligands offers insights into enhancing NK cell-mediated tumor eradication. This review explores the epigenetic modifications governing the expression of activating NKG2D ligands and discusses clinical trials investigating NK cell-based immunotherapies, highlighting their potential as effective cancer treatment strategies. Case studies examining the safety and effectiveness of NK cell therapies in different cancer types, such as acute myeloid leukemia (AML) and non-small cell lung cancer (NSCLC), demonstrate promising outcomes with minimal toxicity. These findings underscore the therapeutic prospects of epigenetic modulation of NKG2D ligands and NK cell-based immunotherapies as effective cancer treatment strategies. Future research in the advancement of personalized medicine approaches and novel combination therapies with NK cell will further improve treatment outcomes and provide new therapeutic options for treating patients with various types of cancer.